Diffusion tensor imaging of the human cerebellar pathways and their interplay with cerebral macrostructure - Keser, Zafer; Hasan, Khader M.; Mwangi, Benson I.; Kamali, Arash; Ucisik-Keser, Fehime Eymen; Riascos, Roy F.; Yozbatiran, Nuray; Francisco, Gerard E.; Narayana, Ponnada A. (Frontiers in Neuroanatomy, 2015)
Cerebellar white matter connections to the central nervous system are classified functionally into the spinocerebellar, vestibulocerebellar, and cerebrocerebellar subdivisions. The Spinocerebellar (SC) pathways project from spinal cord to cerebellum, whereas the vestibulocerebellar (VC) pathways project from vestibular organs of the inner ear. Cerebrocerebellar connections are composed of feed forward and feedback connections between cerebrum and cerebellum including the cortico-ponto-cerebellar (CPC) pathways being of cortical origin and the dentate-rubro-thalamo-cortical (DRTC) pathway being of cerebellar origin. In this study we systematically quantified the whole cerebellar system connections using diffusion tensor magnetic resonance imaging (DT-MRI). Ten right-handed healthy subjects (7 males and 3 females, age range 20-51 years) were studied. DT-MRI data were acquired with a voxel size = 2mm x 2mm x 2 mm at a 3.0 Tesla clinical MRI scanner. The DT-MRI data were prepared and analyzed using anatomically-guided deterministic tractography methods to reconstruct the SC, DRTC, fronto-ponto-cerebellar (FPC), parieto-ponto-cerebellar (PPC), temporo-ponto-cerebellar (TPC) and occipito-ponto-cerebellar (OPC). The DTI-attributes or the cerebellar tracts along with their cortical representation (Brodmann areas) were presented in standard Montréal Neurological Institute space. All cerebellar tract volumes were quantified and correlated with volumes of cerebral cortical, subcortical gray matter (GM), cerebral white matter (WM) and cerebellar GM, and cerebellar WM. On our healthy cohort, the ratio of total cerebellar GM-to-WM was 3.29 ± 0.24, whereas the ratio of cerebral GM-to-WM was approximately 1.10 ± 0.11. The sum of all cerebellar tract volumes is 25.8 ± 7.3 mL, or a percentage of 1.52 ± 0.43 of the total intracranial volume.